Exploring buyer-seller dyadic perceptions of technology and relationships: Implications for Sales 2.0. Issue 1 (14th March 2016) - Rocco, Richard A.; Bush, Alan J.
Abstract : Purpose: – This paper aims to understand an emerging paradigm for business-to-business selling, Sales 2.0, which connects various enabling technologies within leading sales processes to drive improved business and relational outcomes. In the context of Sales 2.0, this paper addresses the need for buyer–seller dyadic sales research in the literature and highlights the importance of understanding buyer and seller perspectives regarding technology expectations and relationship-building performance. Design/methodology/approach: – This research utilizes a dyadic (salesperson–customer) data collection methodology, involving 74 matched salesperson and customer responses (37 dyads) to an online survey. Existing salesperson (self-report) measures of customer technology expectations and relationship-building performance with customers were utilized and adapted to provide dyadic measures to test for buyer–seller perceptual differences. Findings: – The dyadic data analysis supports the presence of significant perceptual differences between the salesperson and their customer, respective of customer technology expectations and relationship-building performance measures. In particular, the analysis reveals bidirectional perceptual differences for the two measures, whereas the salesperson underestimates the importance of their customer's technology expectations, but overestimates their relational performance relative to their customers. Originality/value: – As technology continues to transform salesperson interactions with customers, the value of capturing a deeper understanding about those interactions increases. This study uses matched salesperson–customer dyads from a health-care sales organization to provide researchers and practitioners with insightful findings with respect to buyer–seller interactions and perceptual differences. Further, the research uniquely advances dyadic measures of customer technology expectations and relationship-building performance with customers to advance sales research in the context of Sales 2.0.